THE EFFECT OF CHANGES IN THE MAIN CHARACTERS PERSONALITY TOWARDS SOCIAL SETTING IN LOIS LOWRYS THE GIVER - Khairulsyah S; Ni Made Widisanti S; Tetty Yukesti (Universitas Pakuan, 2021)
The title of this research is